Analysis of clinical data of different endometrial pathological types in perimenopausal women with abnormal uterine bleeding - Wang, Li; Quan, Shimin; Bai, E.; Yang, Xiaofeng (Frontiers in Oncology, 2024)
Objective: Early detection and diagnosis are important for improving the therapeutic effect and quality of life in patients with endometrial cancer (EC). This study aimed to analyze the clinical data of different endometrial pathological types in perimenopausal women with abnormal uterine bleeding (AUB) in order to provide evidence for the prevention and early diagnosis of EC. Methods: A total of 462 perimenopausal women with AUB were enrolled in this prospective observational study. Endometrial biopsy was performed in patients with suspected endometrial lesions. According to the pathological examination results, the patients were divided into endometrial polyp group (EP) (n=71), endometrial hyperplasia without atypia group (EH) (n=59), atypical endometrial hyperplasia (AEH) (n=36) and EC group (n=27). The history risk factors and ultrasonic imaging characteristics of endometrium among the four groups were compared. Results: Twenty-seven women were diagnosed with EC (5.84%). The prevalence rate of AEH and EC in women of 51-55 years old group were significantly higher than that in women of 40-45 years old group and 46-50 years old group (P<0.05). The age, BMI and history of diabetes gradually increased with the development of endometrial pathological types. In addition, the correlation index of endometrial blood flow increased gradually, and the proportion of uneven endometrial echo, unclear endometrial–myometrial junction (EMJ) and ovarian cyst also increased gradually. However, no statistically significant difference was found when comparing endometrial thickness (ET) and endometrial volume (EV) among endometrial pathological groups (P>0.05). The ET, EV, endometrial vascularization index (VI), endometrial flow index (FI) and vascularization flow index (VFI) in ovarian cyst group were significantly higher (P<0.05), and the proportion of uneven endometrium echo and unclear EMJ were significantly higher compared with non-ovarian cyst group (P<0.05). Conclusions: The most common cause of perimenopausal women with AUB was benign endometrial lesions. However, women aged 51–55 years old with endometrial high risk factors and ovarian cyst should be alert to AEH and EC. Endometrial biopsy need to be performed to determine endometrial malignancy in necessity.